Magnetomotive photoacoustic imaging: in vitro studies of magnetic trapping with simultaneous photoacoustic detection of rare circulating tumor cells. Issue 6 (18th February 2013) - Wei, Chen‐wei; Xia, Jinjun; Pelivanov, Ivan; Jia, Congxian; Huang, Sheng‐Wen; Hu, Xiaoge; Gao, Xiaohu; O'Donnell, Matthew; Ntziachristos, Vasilis
Abstract Photoacoustic (PA) imaging has been demonstrated to be a promising modality in molecular imaging for detection of nanoparticle‐targeted diseased cells or tissues. However, intrinsic absorbers, such as blood, produce strong PA background signals that severely degrade the detection sensitivity and specificity of targeted objects. Magnetomotive photoacoustic (mmPA) imaging, a newly developed molecular imaging modality, introduced dynamic manipulation into traditional PA imaging. Unlike conventional PA imaging, magnetomotive manipulation with simultaneous ultrasound/PA imaging of agents incorporating magnetic nanoparticles enables direct visualization of the signal generating object and can dramatically reduce background signals from strong optical absorbers. This paper briefly reviews recent developments in mmPA imaging, including uses of composite contrast agent, design of magnet system, and data processing for motion filtering. The use of mmPA imaging in detecting rare circulating tumor cells in blood vessels, which remains a big challenge for real‐time in vivo examination using current methodologies, was also addressed. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)